The Effect of World Trade Center Exposure on the Timing of Diagnoses of Obstructive Airway Disease, Chronic Rhinosinusitis, and Gastroesophageal Reflux Disease - Liu, Xiaoxue; Yip, Jennifer; Zeig-Owens, Rachel; Weakley, Jessica; Webber, Mayris P.; Schwartz, Theresa M.; Prezant, David J.; Weiden, Michael D.; Hall, Charles B. (Frontiers in Public Health, 2017)
Objectives In a cohort of rescue/recovery workers exposed to the dust that resulted from the collapse of the World Trade Center (WTC), we assessed how a diagnosis of obstructive airways disease (OAD) affected the likelihood of a subsequent diagnosis of chronic rhinosinusitis (CRS) or gastroesophageal reflux disease (GERD). We also assessed whether OAD acted as a mediator of the association between exposure to the WTC rescue/recovery effort and CRS and GERD diagnoses. Methods In this prospective cohort study, we analyzed Fire Department of the City of New York (FDNY) physician diagnoses of OAD, CRS and GERD that were first documented between September 11, 2001 and September 10, 2011 among 8,968 WTC-exposed firefighters. We used piecewise exponential survival models to evaluate whether OAD was a risk factor for either CRS or GERD and to assess OAD as a possible mediator. Results An OAD diagnosis significantly increased the risks for subsequent CRS (relative rate [RR]: 4.24; 95% CI: 3.78-4.76) and GERD (RR: 3.21; 95% CI: 2.93-3.52) diagnoses. Further, 21% of the WTC exposure effect (high vs. low intensity) on GERD and 13% of the effect (high vs. low intensity) on CRS were mediated by a prior OAD diagnosis. Conclusions Individuals with an OAD diagnosis had elevated risks for subsequent diagnoses of CRS or GERD. Part of the effect of WTC exposure on CRS and GERD diagnoses is mediated by prior diagnoses of OAD; this mediation effect of OAD may reflect biological pathways or healthcare utilization practices.